2021
DOI: 10.3920/jiff2020.0050
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional value of insects and ways to manipulate their composition

Abstract: This article reports on the nutrients present in insects and factors affecting their variability. Data on protein content and amino acid profiles of a variety of insect species are discussed and their amino acid profiles compared to nutrient requirements of growing broiler chicks, catfish, trout, swine, and human adults and young children. Both in vitro and in vivo protein digestibility data for a variety of insect species is presented and factors affecting these data are discussed. Furthermore, the fat conten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
135
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(146 citation statements)
references
References 212 publications
(315 reference statements)
9
135
1
1
Order By: Relevance
“…The variability observed among the results of the different studies regarding the body composition of Z. morio individuals may be due to the various diets used for its rearing ( Payne et al 2016 , Oonincx and Finke 2020 ). Several studies with other insect species have shown that diet is a major determinant with regard to the insect body nutrient composition ( Oonincx and van der Poel 2010 , Danieli et al 2019 ).…”
Section: Nutritional Valuementioning
confidence: 99%
“…The variability observed among the results of the different studies regarding the body composition of Z. morio individuals may be due to the various diets used for its rearing ( Payne et al 2016 , Oonincx and Finke 2020 ). Several studies with other insect species have shown that diet is a major determinant with regard to the insect body nutrient composition ( Oonincx and van der Poel 2010 , Danieli et al 2019 ).…”
Section: Nutritional Valuementioning
confidence: 99%
“…Another issue that companies must deal with is whether they can optimise the genetic make-up of their population to enhance production, waste conversion, and nutritional values. The other question for companies is the nutritional composition of the insects (whether this can be improved; see the article of Oonincx and Finke (2021).…”
Section: Optimising Rearing Processesmentioning
confidence: 99%
“…They discuss the value of such information when breeding a population in captivity while attempting to optimise its genetic makeup as a means to enhance production, waste conversion, and nutritional value. Oonincx and Finke (2021) in this issue provide details of how insects, much like other livestock, can be manipulated to a certain extent in terms of their nutritional composition. The same authors previously gave an overview of the (a) biotic factors that may influence nutrition (Finke and Oonincx, 2014).…”
Section: Insect Breedingmentioning
confidence: 99%
See 1 more Smart Citation
“…A core issue with insect rearing and a major concern is colony health (Maciel-Vergara et al, 2021). While insects can be mass produced, manipulating their nutritional value is a key question (Oonincx and Finke, 2021). Furthermore, what is the role of genetics in improving the performance of mass produced insects (Eriksson and Picard, 2021)?…”
mentioning
confidence: 99%